Auriculotherapy for the intervention effect of chronic heart failure: a systematic review and meta-analysis - Luo, Zhifang; Wang, Lin; Yao, Lei; Wen, Xiaoyan (Frontiers in Cardiovascular Medicine, 2026)
BackgroundAuriculotherapy is a complementary therapy known to improve quality of life in various diseases; however, its clinical application in the treatment of chronic heart failure (CHF) remains limited, partly due to the lack of standardized efficacy evaluation indicators.MethodsRelevant randomized controlled trials on CHF were systematically searched from database inception to November 2025. Two reviewers independently screened studies, extracted data, and assessed study quality. Any disagreements were resolved by consensus with the assistance of a third reviewer. Meta-analyses were conducted using RevMan 5.4.ResultsA total of 24 studies involving 2,387 patients were included in the study. The results of meta-analysis demonstrated that auriculotherapy combined with conventional treatment improved the effective rate of cardiac function improvement [odds ratio (OR) = 3.92, 95% confidence interval (CI): 2.86–5.38, P < 0.00001], increased left ventricular ejection fraction [mean difference (MD) = 4.07, 95% CI: 3.57–4.58, P < 0.00001], reduced left ventricular end-diastolic diameter (MD = −4.27, 95% CI: −4.98 to −3.56, P < 0.00001), and prolonged 6-min walking test distance (MD = 65.11, 95% CI: 62.55–67.68, P < 0.00001). It also reduced the Minnesota Living with Heart Failure Questionnaire score (MD = −7.29, 95% CI: −8.52 to −6.06, P < 0.00001). The incidence of adverse reactions did not differ significantly between groups (OR = 0.55, 95% CI: 0.27–1.10, P = 0.09).ConclusionThe available evidence suggests that auriculotherapy is a safe adjunctive therapy for CHF, capable of improving overall clinical effectiveness, enhancing cardiac function, and improving exercise capacity and quality of life.Systematic Review RegistrationPROSPERO CRD42024621500.